A Framework for Assessing Accountability in Collaborative Governance: A Process-Based Approach. Issue 1 (10th January 2022) - Lee, Seulki; Ospina, Sonia M
Abstract: Despite the complexities involved around the accountability mechanisms of collaborative governance, little is known about how to assess accountability at the network level and disentangle possible accountability deficits. This study first explicates the nature of collaborative governance accountability in contrast to accountability in traditional public administration and market-based governance. The analysis shows how collaborative governance accountability is distinctive: (a) accountability relationships shift from bilateral to multilateral; (b) horizontal as well as vertical accountability relationships are involved; (c) not only formal standards but also informal norms are used; and (d) accountability challenges move from control/audit issues to trust-building and paradox management issues. We then propose a framework for accountability in collaborative governance, drawing its dimensions from the process-based accountability research. Our framework builds on three dimensions of collaborative accountability—information, discussion, and consequences—and elaborates on their components and indicators. Based on the framework, questions to guide future research are provided, focusing on tensions and paradoxes that can arise in each process dimension as primary accountability challenges in collaborative contexts.